Modeling Acute ER Stress in Vivo and in Vitro. Issue 4 (April 2017) - Abdullahi, Abdikarim; Stanojcic, Mile; Parousis, Alexandra; Patsouris, David; Jeschke, Marc G.
Abstract : ABSTRACT: The endoplasmic reticulum (ER) is a critical organelle that synthesizes secretory proteins and serves as the main calcium storage site of the cell. The accumulation of unfolded proteins at the ER results in ER stress. Although the association between ER stress and the pathogenesis of many metabolic conditions have been well characterized using both in vivo and in vitro models, no standardized model concerning ER stress exists. Here, we report a standardized model of ER stress using two well-characterized ER stress-inducing agents, thapsigargin and tunicamycin. Our aim in this current study was 2-fold: to characterize and establish which agent is optimal for in vitro use to model acute ER stress and to evaluate which agent is optimal for in vivo use. To study the first aim we used two well-established metabolic cell lines; human hepatocellular carcinoma (HepG2s) and differentiated mouse adipocytes (3T3-L1). In the second aim we utilized C57BL / 6J mice that were randomized into three treatment groups of sham, thapsigargin, and tunicamycin. Our in vitro results showed that tunicamycin worked as a rapid and efficacious inducer of ER stress in adipocytes consistently, whereas thapsigargin and tunicamycin were equally effective in inducing ER stress in hepatocytes. In regards to our in vivo results, we saw that tunicamycin was superior in not only inducing ER stress but also recapturing the metabolic alterations associated with ER stress. Thus, our findings will help guide and inform researchers as to which ER stress agent is appropriate with regards to their model. Abstract : Supplemental Digital Content is available in the text